Respuesta :

Answer:

I'm glad you asked!

Step-by-step explanation:

OK,let's simplify the number for a equivalent expression.

[tex]4+2(1+3x)[/tex]

Distribute:

[tex]=4+(2)(1)+(2)(3x)[/tex]

[tex]= 4+2+6x[/tex]

Combine Like Terms:

[tex]=4+2+6x[/tex]

[tex]=(6x)+(4+2)[/tex]

[tex]=6x+6[/tex]

The Final Answer is : [tex]6x+6[/tex]

The expression that is equivalent to 4+2(1+3x) is 6x+6.

What is an Algebraic expression?

Mathematical expressions that are made up of constants, variables, and coefficients that are combined using algebraic operations such as multiplication, addition, subtraction, and division are called Algebraic expressions.

How do simplify the algebraic expression?

Given, 4+2(1+3x)

Firstly distribute 2(1+3x) to get 2+6x then,

4+2(1+3x)

=4+2+6x

=6x+6

Thus, 4+2(1+3x)=6x+6

For more simplification visit- https://brainly.com/question/953809?referrer=searchResults

#SPJ2